TEORI PROSPEK DAN KONSERVATISMA LAPORAN KEUANGAN - Muhamad Safiq; Jogiyanto HM; Supriyadi Supriyadi; Ertambang Naha (Universitas Pakuan, 2019)
This research was aimed to test the influence of incentive contract framing (framing effect) and class action (certainty effect) to financial reporting decision. Beside that, this research also investigated the interaction influence between framing effect and certainty effect. This research used laboratorium experiment design 2x2 between subjects. Experiment subjects were business students (MM and Maksi) Gadjah Mada University who were acted as management (CFO) with certain criteria. Research results showed that there was an influence of incentive contract framing and class action (litigation) to management’s (CFO) financial reporting decision. Subjects who were the insentive contract framed positively, tended to prepare more conservative financial statement. Vice versa, subjects who were the incentive contract framed negatively, tended to become risk taker, so that management (financial director) tended to prepare less conservative financial statement. But, the interaction result between incentive contract framing variable with class action (litigation) showed insignificant result. measurement problems are thought to affect these insignificant. Future studies are expected to give more attention to these problems.